(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and in Him we seek help, and prayers and peace be upon the one who was sent as a mercy to the worlds, our ProphetMuhammed (may God bless him and grant him peace), his family and his companions at all times, and may God’s curse be upon the wrongdoersThose who offend God and His Messenger from among the Jews and the hypocrites and those who follow their actions until the Day of Judgment, and may God protect usFrom polytheism and its people, and from the accursed Satan, he hears and responds.After this, a research entitled The Cursed in the Holy Qur’an is an objective study, in which I dealt withA statement of whom God has cursed in His clear book, explaining the reason for the curse and citing what is mentioned in the verses mentionedshown.The nature of the research required that it be divided into a preface and six chapters.I mentioned in the preface the definition of the curse linguistically and idiomatically.In the first chapter, I mentioned the first category of the cursed, and they are people whom God told us inThe Qur’an, and in the two chapters the verses with which God cursed the people of Ad and the people of Pharaoh, citing the sayings ofinterpreters in clarifying their meanings.In the second chapter, I dealt with the cursed among those who were given the Book before, and explained inThe third chapter deals with the verses by which God cursed the Jews, explaining the reasons for the curse. And I made it clear who was cursed by GodPeople have attributes and actions in them, in eight topics, and I cited what was proven in the purified Sunnah.Because it is the second source of legislation.